Rights and Position of Adopted Children According to KHI and Common LAW - Silfi Rizkina; Arief Suryono (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
In Indonesia, three inheritance law systems apply namely civil, Islamic, and customary inheritance law. These three legal systems are implemented because there is no national inheritance law that can regulate all Indonesian people. This study aims to explain the position and inheritance rights of adopted children in the view of the Compilation of Islamic Law (KHI) and customary law. This research is descriptive normative legal research. Considering that the object of this study is the issue of the position and inheritance rights of adopted children as seen from Islamic inheritance law and customary law (jurisprudence), this type of research uses a normative juridical approach with a library research pattern. The research results showed that according to KHI, adopted children are not recognized as heirs of their adoptive parents, because the main principle of Islamic inheritance is a blood relationship. Meanwhile, according to Supreme Court jurisprudence, adopted children are equated with biological children and are considered capable of inheriting the assets of their adoptive parents.